Tools to measure health literacy among Chinese speakers: A systematic review. Issue 5 (May 2020) - Zhang, Ling; Ding, Ding; Fethney, Judith; Neubeck, Lis; Gallagher, Robyn
Highlights: We identified ten health literacy tools that are validated in Chinese. Tools varied in measured components, psychometric properties and strength. We suggest selecting appropriate tools for clinical or research purposes. Tools to measure health literacy among Chinese speakers: a systematic review. Abstract: Objective: Health literacy measurement can identify healthcare consumers' needs and help inform healthcare service delivery. The objective of this review is to identify and evaluate tools to measure health literacy among Chinese speakers. Methods: A systematic literature search was undertaken in nine databases, both English and Chinese, on articles published from the databases' inception to May 2018, addressing health literacy among Chinese speakers. Results: Ten health literacy instruments in the Chinese language were reported in 17 studies, of which ten were published in English and seven in Chinese. Of the 17 studies, six reported on a new instrument, while the remainder reported on derivative instruments. All, except for one, are self-administered. These studies applied various implicit or explicit conceptual or operational health literacy definitions. The psychometric strength varied across the instruments. Conclusions: A number of instruments are available for assessing health literacy among Chinese speakers. Careful selection is recommended, given the variation in components and psychometric properties assessed. Practice implications: This review can be used by healthcare providers and researchers to select effective health literacy tools to examine patients' ability to understand and apply health information so that services can be more appropriately tailored to Chinese speaking patients.